2001
DOI: 10.1007/s007050170201
|View full text |Cite
|
Sign up to set email alerts
|

MMTV-like env gene sequences in human breast cancer

Abstract: We have previously detected an MMTV env gene-like 660 bp sequence in 38% of human breast cancers, but not in normal tissues or other tumors. In this communication we report the sequences from eleven tumors and three breast cancer cell lines, and compare them to four strains of MMTV and to the known endogenous retroviral sequences. The breast cancer sequences were highly homogenous to the MMTV's, but not to the endogenous sequences suggesting an exogenous origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
148
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(158 citation statements)
references
References 17 publications
8
148
1
1
Order By: Relevance
“…Although this is the first report demonstrating evidence for betaretrovirus infection in patients with PBC, our findings are concordant with other investigators who have provided immunochemical, serologic, molecular hybridization and electron microscopy evidence of a human betaretrovirus infection in patients with breast cancer and healthy subjects (13,18,(25)(26)(27)(28). Full-length proviral betaretroviral sequences have been cloned from one PBC patients' peri-portal lymph node and two human breast cancer samples and fluorescent in situ hybridization studies have shown betaretrovirus integration in human chromosomes from metastatic breast cancer cells (ref.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although this is the first report demonstrating evidence for betaretrovirus infection in patients with PBC, our findings are concordant with other investigators who have provided immunochemical, serologic, molecular hybridization and electron microscopy evidence of a human betaretrovirus infection in patients with breast cancer and healthy subjects (13,18,(25)(26)(27)(28). Full-length proviral betaretroviral sequences have been cloned from one PBC patients' peri-portal lymph node and two human breast cancer samples and fluorescent in situ hybridization studies have shown betaretrovirus integration in human chromosomes from metastatic breast cancer cells (ref.…”
Section: Discussionsupporting
confidence: 92%
“…These studies do not directly address a causal relationship between microbe and disease but they support the numerous reports documenting the presence of a betaretrovirus infection in humans (13,18,(25)(26)(27)(28). In this regard, we have devised a coculture model that can be used to test Koch's postulates in vitro by using either pure isolates or transfected DNA of the human betaretrovirus.…”
Section: Discussionmentioning
confidence: 73%
“…During the 1970s, MMTV was suggested to play a role in the etiology of human breast cancer when claims were first made that MMTV antigens were involved in this disease (3). A new wave of interest in this issue started in the mid-1990s when MMTV DNA sequences were first identified, using PCR technology, in 38% of human breast cancer samples, but not in healthy tissue (4). Despite the lack of incontrovertible evidence for a causal relationship between MMTV and breast cancer and doubts whether MMTV is a tumor virus or just a "rumor" virus in the context of this disease (ref.…”
Section: Introductionmentioning
confidence: 99%
“…MMTV env gene plasmid and MCF-7 and MB-MDA-231 cell lines were used as a positive control, as described in previous studies. 1,2,11,17 The viral sequence was first amplified by regular PCR; then, PCR products were hybridized with an internal probe by PCR Southern hybridization; finally, real-time PCR was performed. We were unable to detect the viral sequence in the cell lines or in the breast tumor tissues despite robust amplification from the plasmid control.…”
mentioning
confidence: 99%